A novel C-type lectin (CLEC12B) from Nile tilapia (Oreochromis niloticus) is involved in host defense against bacterial infection. Issue 131 (December 2022) - Zhang, Zhiqiang; Niu, Jinzhong; Li, Qi; Huang, Yongxiong; Jiang, Baijian; Li, Xing; Jian, Jichang; Huang, Yu
Abstract: C-type lectin (CLEC) is a family of carbohydrate-binding protein that has high affinity for calcium and mediates multiple biological events including adhesion between cells, the turnover of serum glycoproteins, and the innate immune system's reaction to prospective invaders. However, it's ill-defined for how CLEC effects bony fish's innate immunity to bacterial infection. Therefore, CLEC12B, a member of the C-type lectin domain family, was found in Nile tilapia ( Oreochromis niloticus ) and its functions in bacterial infection were examined. The OnCLEC12B consist of a C-type lectin domain, a transmembrane domain, and a hypothetical protein of 308 amino acids that encoded by 927 bp basic group. Besides, the OnCLEC12B protein have a series of highly conserved amino acid sites with other CLEC12B proteins. Subcellular localization showed that OnCLEC12B located in cell membrane. Transcriptional levels investigation showed that OnCLEC12B was extensively expressed in all selected organs and has high expression in the liver. The transcriptional levels of OnCLEC12B were induced by Streptococcus agalactiae and Aeromonas hydrophila in the liver, spleen, head kidney, brain, and intestine. Afterward, in vitro study revealed that several kinds of pathogens could be bound and agglutinated by recombinant protein of OnCLEC12B (rOnCLEC12B). Moreover, rOnCLEC12B could not only promote the proliferation of monocytes/macrophages but also encourage its phagocytosis on S.agalactiae and A.hydrophila, and its over-expression could significantly suppress the activation of the NF-κB pathway. Summarily, our results indicated that OnCLEC12B gets involved in fish immunization activities to pathogens infection. Highlights: CLEC12B was identified in the Nile tilapia. The expression of OnCLEC12B was upregulation after being challenged by Streptococcus agalactiae and Aeromonas hydrophila . Variety of bacterial pathogens was bound and agglutinated with rOnCLEC12B. The phagocytosis of monocytes/macrophages for bacterial pathogens could be markedly enhanced by rOnCLEC12B.